Hubungan Kebijakan Pandemi COVID-19 Terhadap Faktor Pernikahan Usia Remaja Kecamatan Pringgabaya, Lombok Timur, NTB - Nurwaningsih Ningsih; Ika Wijayanti; Ratih Rahmawati (Prodi Sosiologi Universitas Mataram, 2021)
The study aims to know the relationship of pandemic COVID-19 policy toward teenager marriage factor. The method used in this study is quantitative method with associative approch. Data collection techniques using questionnaires, while data analysis techniques use spearman correlation analysis the results showed that there was a significant relationship between COVID-19 Pandemic policy toward teenage marriage factor with relationship rate off 8,11%. Also Policy in pandemic covid-19 raises the awareners of healthy and clean life exercise a healthy lifestyle by following the healthy protocols applied by the goverment. But on the others hand, there is an event of latent or an uncological function of the policy of COVID-19 pandemic is one of the factor behind teenage marriage, where the policies are related to social restrinctions and network learning (online), socioeconomic, cultural and environment become the factor that cause teenagers in marriage.